Evaluation in education. - Choppin, Bruce; Postlethwaite, T. Neville (Pergamon Press, 1979)
Evaluation in Education, Volume 1 is a series of monographs that compiles various studies that cover the methodologies and techniques utilized in evaluating student performance in various educational systems.